Cassava Manihot esculenta Crantz growth indices, root yield and its components in upland and inland valley agroecologies of Sierra Leone - Lahai, M.T.; George, J.B.; Ekanayake, I.J. (Wiley, 1999)
Cassava is predominantly an upland crop that is also cultivated in inland valley swamps (IVS). Identifying physiological traits that can withstand excess moisture stress can aid in the selection and use of stable cassava cultivars in IVS. Three cassava cultivars were evaluated for growth and yield in the upland and IVS ecologies in the 1993–94 crop seasons using a randomized complete block design. In the upland, 80/40 outyielded 87/29 and ‘coco', while in the IVS, 87/29 had the highest yield. Highest yielding cultivars in each ecology also had the highest tuberous root bulking rate (TBR), dry matter (DM) production, crop growth rate (CGR), relative growth rate, net assimilation rate (NAR), leaf area index, leaf production rate and leaf life. Positive correlations between these parameters and tuberous root yield were noted. High yield of 87/29 in IVS was partly due to its low tuberous root rotting. High root rotting in 80/40 was partly as a result of the greater depth of tuberous roots in the soil (0.3–0.6 m) as compared to the other cultivars (0.15–0.3 m) where roots were in contact with stressful water levels earlier than others. The yield and yield components, growth and leaf characters were all drastically reduced when the cultivars were grown in IVS as compared to upland. For example, root yields of ‘coco', 87/29 and 80/40 were reduced by 53 %, 60 % and 92 %, respectively, in IVS. Selection of cassava cultivars with longer leaf life and leaf area maintenance leading to high CGR, TBR, NAR and harvest index (in IVS and upland), coupled with a shallow tuberous root formation zone (in IVS) can give higher root and leaf yields in the two ecologies.